Mexico after general elections 2012 Successful reforms or wishful thinking? - Khamidova, Aziza; Němec, Jan, 1980 srpen 23.-; Paulenková, Kristína; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
The central topic of analysis in the master thesis is the general elections in Mexico in 2012 and their influence on the ongoing reform process in the country. The emphasis is put on the effect of conducted reforms and the extent to which they are influenced by the separation of powers in the Mexican presidential system, the Congress itself, the power of the presidents the role of the political parties, the nature of the presidential systems in general, as well as the civil society i.e. the public. There has been a certain amount of criticism that the new, PRI political strategy is simply a portrait of the so called "dinosaur elite" and it is not working towards completing the needs of the people. The aim of the master thesis therefore is firstly to define the nature of the presidential systems, to elaborate any potential deadlocks and limitations that the system might impose in the reform process, and afterwards to represent the extent to which different factors influence the actual reform process in Mexico lead by the President Nieto. The research question aims to respond whether the current structural reforms are well maintained in terms of their effectiveness and in terms of gaining support from the remaining parties in the Congress, or the situation needs to be approved from another angle. In other words, it is crucial to show to what extent the newly elected political leadership in Mexico, as of 2012, had so far reformed the country in regard of strengthening the democracy, improving the economic situation by reducing the growing income inequality amongst the people, as well as working on the security improvement of the country.
Vedoucí práce: Jan Němec
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses